Implementasi Deep Learning dalam Edukasi Lingkungan dan Kesadaran Ekologis pada Peserta Didik SMA Negeri 1 Siantan - Nafisatul Fuadah; Widia Nurmadyah (Advances In Education Journal, 2025)
The decline in biodiversity due to climate change, pollution, and deforestation necessitates active participation from the younger generation. This study aims to assess students' ecological awareness through a deep learning approach in schools, hypothesizing that its three key orientations can foster pro-environmental behavior. A mixed-methods approach was employed with a sample of 48 students. Data were collected through Likert-scale questionnaires and participatory observation. The results revealed: 0 students "strongly disagreed," 2 "disagreed," 6 were "neutral," 28 "agreed," and 14 "strongly agreed" regarding the effectiveness of deep learning. The findings demonstrate that this approach facilitates in-depth learning beyond the classroom, enhances students' sensitivity to their school environment, and encourages protective and conservation-oriented actions. The study concludes that deep learning is effective in cultivating ecological awareness and pro-environmental behavior among students, with practical implications for experiential, context-based environmental education.